Situation : Collaborations, collectives and artist networks from Sydney, Singapore, Berlin. - Storer, Russell; Pulie, Elizabeth; Storer, Russell; Museum of Contemporary Art, Sydney; Exhibition. Situation : Collaborations, collectives and artist networks from Sydney, Singapore, Berlin. Museum of Contemporary Art Sydney 2005 (Sydney : Museum of Contemporary Art Sydney, 2005)
Barney, Simon ; Gawronski, Alex ; Goffman, Sarah ; Kay, Anne ; Kelly, Lisa ; Polkinghorne, Jane ; Pulie, Elizabeth ; Hiah Buang Hoe, Jeremy ; Koh Nguang How ; Kai Lam Hoi Lit ; Lee Wen ; Tang Dawu ; Yasin, Juliana ; Yit Mun Khwan, Agnes ; Müller, Ariane ; Nellemann, Lise ; Saebjörnsson, Egill ; Sehgal, Tino ; Wilcke, Jole
Situation: Collaborations, collectives and artist networks from Sydney, Singapore and Berlin, Museum of Contemporary Art, Sydney, 6 June - 21 August 2005
Engels
boek
Keywords: Berlin; Singapore; Sydney